2007
DOI: 10.1093/humrep/del501
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic capacity of transvaginal hydrolaparoscopy to predict spontaneous pregnancy

Abstract: THL is a feasible technique. Its capacity to predict spontaneous ongoing pregnancy is comparable to that of laparoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 13 publications
5
8
0
Order By: Relevance
“…The classic colpotomy technique is very simple for specialized vaginal surgeons, and the operating time for this procedure is shorter than that for endoscopic colpotomy; however, this approach can be difficult for inexperienced surgeons and is occasionally unsuccessful. Access to the pouch of Douglas has been achieved in 88.6%-100% of reported cases [14][15][16][17]. In the present study, successful access to the pelvis was achieved in 138 of 140 cases (98.6%).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The classic colpotomy technique is very simple for specialized vaginal surgeons, and the operating time for this procedure is shorter than that for endoscopic colpotomy; however, this approach can be difficult for inexperienced surgeons and is occasionally unsuccessful. Access to the pouch of Douglas has been achieved in 88.6%-100% of reported cases [14][15][16][17]. In the present study, successful access to the pelvis was achieved in 138 of 140 cases (98.6%).…”
Section: Discussionsupporting
confidence: 50%
“…Major complications, such as perforation of the bowel or uterine wall, life-threatening bleeding, abscesses, and sepsis, have been reported to occur in 0%-2.2% of cases [14][15][16][17]20,21]. In the present study there were no major complications, and blood loss was minimal during surgery.…”
Section: Discussionsupporting
confidence: 45%
“…More et al [14] reported a pain score of 4.2 on a VAS scale and showed that 96 % of the patients would undergo again the procedure. In a prospective study, Van Tetering et al [15] showed that the capacity of THL to predict spontaneous pregnancy was similar to laparoscopy. In the same study the acceptability of the procedure was also evaluated and showed that mean tolerability VAS score was low, indicating a high acceptability.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, a multicentre randomised controlled trial4 demonstrated that the routine use of HSG at an early stage of infertility work up, before laparoscopy and dye, does not influence the cumulative pregnancy rate compared with the routine use of laparoscopy and dye alone. However, HSG is an efficient method which is less invasive and less costly than laparoscopy,5 and transvaginal hydrolaparoscopy 6. The main disadvantages of HSG are that it is not possible to confirm adhesions and endometriosis, and that it is a painful procedure 7 8.…”
Section: Introductionmentioning
confidence: 99%